Removal of phenol from water using hydrophobic eutectic solvents - Kek, Ming Xuan (2023)
Phenolic compounds are one of the major pollutants in industrial wastewater. Conventionally, organic solvents, which are normally toxic, highly flammable, and have high vapour pressure, are used in the liquid-liquid extraction process to remove phenolic compounds in industry. A green solvent must be developed to replace such organic solvents due to their unsustainability. The present study focuses on the synthesis of menthol-based hydrophobic eutectic solvents and determines their efficiency in phenol removal. Different types of hydrophobic eutectic solvents were synthesized using lauric acid, myristic acid, and palmitic acid as hydrogen bond donors and selected to perform liquidliquid extraction to remove phenol from water based on their stability. Operating parameters such as initial phenol solution concentration, stirring speed, and solvent-to-solution ratio were examined to analyse their effect on the performance of the solvents. The phenol uptake capacity of the solvents was also determined by performing five cycles of liquid-liquid extraction using the same batch of solvents. From the study, it was found that the hydrophobic eutectic solvents formed with a menthol-to-lauric acid molar ratio of 2:1 (MLA) and a menthol-to-myristic acid molar ratio of 4:1 (MMA) were stable when added to water. MMA generally performed better than MLA, where removal efficiency of 63.68 % and 59.86 % was recorded respectively when 1 g of solvent was used under an initial phenol solution concentration of 2500 ppm with a 700 rpm stirring speed provided. Besides, the removal efficiency dropped slightly when the initial phenol concentration increased from 500 ppm to 2500 ppm. There was also no significant effect recorded when the stirring speed increased from 300 rpm to 1200 rpm. The removal increased drastically when the amount of solvent used increased from 0.1 g to 2 g, from around 10 % to 75 %. It was found that the MMA has a higher capacity of 42.40 mg/g compared to the MLA, which has a capacity of 33.43 mg/g. Several suggestions were made for future studies to help develop hydrophobic eutectic solvents to replace conventional organic solvents.